Switch : how to change things when change is hard - Heath, Chip (Broadway Books, 2010)
In a compelling, story-driven narrative, the Heaths bring together decades of counterintuitive research in psychology, sociology, and other fields to shed new light on how we can effect transformative change. "Switch "shows that successful changes follow a pattern, a pattern you can use to make the changes that matter to you, whether your interest is in changing the world or changing your waistline.